A Highly Efficient Coupled-Inductor SEPIC Topology Based PFC DC–DC Converter for Low Power LED Lighting Systems. Issue 1 (2nd January 2019) - Pal, Somnath; Singh, Bhim; Shrivastava, Ashish
ABSTRACT: This paper deals with the design, simulation, and implementation of a single-stage single ended primary inductance converter (SEPIC) power factor correction (PFC) converter-based light emitting diode (LED) driver useful to operate for wide supply voltage variations. The proposed non-isolated SEPIC converter has been chosen to operate in discontinuous conduction mode (DCM) using pulse frequency modulation (PFM) control scheme to control output current through an LED lamp string. The primary focus of this work is to develop an efficient power converter with improved power quality performances for low power LED lighting systems. The modeling, simulation, and implementation of the proposed driver have been carried out for a 28 W LED string load. To confirm the design of the proposed driver, various power quality performance parameters are analyzed which are found well within the norms of international standard IEC 61000-3-2 of class C equipment throughout the universal AC mains.